Manipulation of solid dosage forms for oral administration to paediatric patients for drug-resistant tuberculosis in South Africa: an observation study - Sheetal Harichander; Varsha Bangalee; Frasia Oosthuizen (BMC, 2024)
Abstract Background Children represent a particularly vulnerable demographic in the context of drug-resistant (DR) tuberculosis (TB) due to their increased likelihood of close contact with adults diagnosed with the disease. Approximately 25 000-30 000 children develop DR-TB annually. While treatment success rates for DR-TB in children surpass those in adults, children and adolescents encounter distinct challenges throughout the diagnosis and treatment of DR-TB (including MDR-TB, Pre-XDR TB, and XDR-TB). Aim To identify current practices in drug administration to children diagnosed with DR-TB where appropriate dosage forms are not available in South Africa. Method An observational study was carried out at the study site to determine how medication prescribed was manipulated and administered by nursing staff to paediatric patients in the wards. Results The observational study identified 8 drugs used in DR-TB at the study site, where some manipulation to the formulation was necessary to enable administration to paediatric patients. Linezolid and para-aminosalicylic acid are the only drugs available and registered in the South Africa in a formulation that is suitable for administration to paediatric patients. Activities carried out by nursing staff to enable the administration of DR-TB medication included cutting capsules and tablets and dissolving the tablet or capsule contents in distilled water to obtain the required suitable dose. Discussion Lack of availability of suitable dosage forms for paediatrics patients results in several challenges, such as additional time required for drug preparation, increased time duration of medication administration, and unpalatability of drugs. These challenges may subsequently affect compliance and therapeutic outcomes of the treatment of paediatric patients, especially as outpatients. Conclusion Research needs to focus on the development of appropriate dosage forms for the paediatric population and focus on identifying cases of DR-TB in children. This will assist in building evidence to advocate for registration of child-friendly dosage forms thereby ensuring a sustainable supply of medication.